Laser-cladding refractory high-entropy alloy coating on surface of titanium alloy and preparation method of laser-cladding refractory high-entropy alloy coating

The high-entropy alloy coating composed of Mo, Ta, Nb, V, and W was prepared by laser cladding, which solved the problem of insufficient wear resistance and high-temperature oxidation resistance of titanium alloy under complex working conditions, and realized the surface of titanium alloy High-strength and high-temperature performance are improved, and low cost is suitable for a variety of application scenarios.

CN119121026APending Publication Date: 2024-12-13KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411261538.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Titanium alloys are difficult to serve for a long time under complex operating conditions, mainly due to their insufficient wear resistance, corrosion resistance and high temperature oxidation resistance. Existing research has not fully demonstrated the advantages of high-entropy alloys in improving these properties of titanium alloy surfaces.

Method used

A high entropy alloy coating consisting of five high melting point metal elements: Mo, Ta, Nb, V and W were prepared by laser cladding. The alloy powder was mixed by vacuum ball milling, and anhydrous ethanol was added to form a slurry, and coated on titanium alloy. The substrate surface and a metallurgical-bound high-entropy alloy coating are formed through laser cladding technology.

Benefits of technology

It significantly improves the strength, hardness and high-temperature oxidation resistance of the surface of titanium alloy, and forms a coating with high hardness, high toughness and excellent high-temperature oxidation resistance, and is low in cost and is suitable for applications in different working conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121026A_ABST
    Figure CN119121026A_ABST
Patent Text Reader

Abstract

The invention provides a titanium alloy surface laser cladding refractory high-entropy alloy coating and a preparation method thereof, and belongs to the technical field of alloy surface coating modification. The preparation method comprises the following steps: weighing metal powder of 15.0-17.0 wt% of Mo, 29.0-31.0 wt% of Ta, 14.0-16.0 wt% of Nb, 7.0-9.0 wt% of V and 31-33 wt% of W, mixing, carrying out vacuum ball milling, and then mixing with absolute ethyl alcohol to obtain slurry; the surface of a titanium alloy matrix is coated with the slurry, then the alloy coating is obtained through drying and laser cladding in sequence, and the coating has high hardness, high strength, high toughness, high plasticity at the low temperature, excellent high-temperature oxidation resistance and the like so as to be better applied under different working conditions; the high-temperature service performance of the titanium alloy can be comprehensively improved, and the surface strength, hardness, high temperature resistance and oxidation resistance of the titanium alloy are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy surface coating modification, and specifically relates to a titanium alloy surface laser cladding refractory high entropy alloy coating and a preparation method thereof. Background Art

[0002] High entropy alloys are a new type of material that has developed rapidly in recent years. Since it was proposed by Ye Junwei and others in 2004, it has attracted widespread attention for its excellent properties, such as low-temperature toughness, high-temperature oxidation resistance, wear resistance and corrosion resistance. It is generally believed that these excellent properties are derived from the four major effects of the alloy, namely the interaction of high entropy effect, lattice distortion effect, slow diffusion effect and cocktail effect. The preparation of high entropy alloys mainly adopts the vacuum melting method. The preparation cost of bulk high entropy alloys is relatively high and cannot be widely used in industrial production. The researchers turned their research direction to the preparation of high entropy alloy coatings. High entropy alloy coatings can avoid the waste of expensive metals and ensure the thickness of the coating. They have high strength and hardness, good high-temperature oxidation resistance, wear resistance and corrosion resistance.

[0003] Poor wear resistance, corrosion resistance and high temperature oxidation resistance are the key issues that restrict titanium alloys from long-term service under complex working conditions. In recent years, more and more researchers have devoted themselves to the field of surface modification of alloy surface coatings, mainly including: laser cladding, vapor deposition, ion implantation and spraying. Among them, laser cladding technology has the advantages of fast heating and cooling, metallurgical bonding between the cladding layer and the substrate, few defects in the cladding layer, and small heat-affected area on the substrate.

[0004] The use of laser cladding technology to prepare high-entropy alloy coatings on alloys can better meet the material needs of scientific and technological development. High-entropy alloys with excellent performance can be used to replace traditional alloys in situations that cannot be met, showing great application potential in aerospace, energy, transportation, and electronic communications.

[0005] At present, the research on high entropy alloy coating by laser cladding on titanium alloy surface by domestic and foreign scholars is still in its infancy. There is a lack of relatively unsystematic research reports from high entropy alloy coating composition design to laser cladding preparation and performance characterization, which fails to fully demonstrate the advantages of high entropy alloy in improving the wear resistance and high-temperature oxidation resistance of titanium alloy surface.

[0006] Therefore, an alloy coating with high strength, high temperature wear resistance and oxidation resistance is needed. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a refractory high-entropy alloy coating laser-clad on the surface of a titanium alloy and a preparation method thereof, which can comprehensively improve the high-temperature service performance of the titanium alloy, enhance its surface strength, hardness, high temperature resistance and oxidation resistance.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] In a first aspect, the present invention provides a refractory high entropy alloy coating by laser cladding on the surface of a titanium alloy, which is prepared from the following metal powders in percentage by mass:

[0010] Mo: 15.0-17.0wt%, Ta: 29.0-31.0wt%, Nb: 14.0-16.0wt%, V: 7.0-9.0wt%, W: 31-33wt%.

[0011] Preferably, the mass percentages of the metal powder are Mo: 16.08wt%, Ta: 28.94wt%, Nb: 15.3wt%, V: 7.98wt%, and W: 31.7wt%.

[0012] In a second aspect, the present invention provides a method for preparing a refractory high entropy alloy coating by laser cladding on the surface of the titanium alloy, comprising the following steps:

[0013] 1) Weighing the metal powder raw materials according to the mass percentage, mixing them, and vacuum ball milling them to obtain a mixed alloy powder;

[0014] 2) mixing the mixed alloy powder with anhydrous ethanol to obtain a slurry;

[0015] 3) The slurry is coated on the surface of the titanium alloy substrate and then dried and laser clad to obtain a high entropy alloy coating.

[0016] Preferably, the vacuum ball milling time in step 1) is 3-5 h.

[0017] Preferably, the particle size of the mixed alloy powder in step 1) is 15-53 μm.

[0018] Preferably, in step 2), the amount of anhydrous ethanol is 5-10% of the mass of the mixed alloy powder.

[0019] Preferably, the coating thickness in step 3) is 1.0-3.0 mm.

[0020] Preferably, in step 3), the drying temperature is 50-100° C. and the drying time is 2-5 h.

[0021] Preferably, the process parameters for laser cladding in step 3) are: laser power of 3500 W, scanning speed of 600 mm / min, spot diameter of 3.0 mm, defocus of 25 mm, argon as protective gas, and gas flow rate of 5 L / min.

[0022] Preferably, in step 3), the titanium alloy substrate is pretreated before coating, and the pretreatment method is: the substrate surface is polished with 400-mesh sandpaper and then degreased.

[0023] More preferably, the titanium alloy substrate is a common titanium alloy, more preferably a Ti-6Al-4V alloy.

[0024] Contains at least the following beneficial technical effects:

[0025] 1. The present invention provides a high entropy alloy coating composed of five high melting point metal elements, namely Mo, Nb, Ta, W and V, which has high hardness, high strength, high toughness, high plasticity at low temperature, and excellent high temperature oxidation resistance, etc., so as to be better applied under different working conditions; it can comprehensively improve the high temperature service performance of titanium alloy, enhance its surface strength, hardness, high temperature resistance and oxidation resistance.

[0026] 2. The coating prepared by laser cladding in the present invention forms a metallurgical bond with the substrate. The coating has good morphology, no obvious holes and cracks, and is a dendritic structure. It can be evenly and densely covered on the outer surface of the substrate, which is beneficial to improving the comprehensive performance of its alloy coating for surface modification.

[0027] 3. The present invention combines the advantages of laser cladding method with high entropy alloy. The prepared coating has high bonding strength with the substrate and excellent performance. It not only has low cost, but also can fully improve the shortcomings of low-cost metal materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a schematic diagram of the prefabricated coating in Example 1 of the present invention;

[0029] Figure 2 is the XRD diffraction pattern of the coating in Example 1 of the present invention;

[0030] Figure 3 This is a microstructure diagram of the bonding area between the coating and the substrate in Example 1 of the present invention;

[0031] Figure 4 This is a curve diagram of the hardness of the coating and the substrate in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0033] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0034] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the main idea or essential features of the present invention. Therefore, from all points of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.

[0035] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0036] It should also be understood that the specific embodiments described above are only used to explain the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes based on the technical solutions and inventive concepts of the present invention, which should be covered by the protection scope of the present invention / invention.

[0037] Example 1

[0038] This embodiment provides a refractory high entropy alloy coating by laser cladding on the surface of a titanium alloy, and the specific steps of preparation are:

[0039] 1) Weigh each metal powder according to mass percentage, specifically:

[0040] Mo: 16.08wt%, Ta: 28.94wt%, Nb: 15.3wt%, V: 7.98wt%, W: 31.7wt%;

[0041] Then the weighed metal powders were mixed and vacuum ball-milled for 3 h to obtain a mixed alloy powder of 35 μm.

[0042] 2) Add 8% by weight of anhydrous ethanol to the mixed alloy powder to obtain a slurry.

[0043] 3) The Ti-6Al-4V alloy plate was polished with 400-grit sandpaper to remove the oxide thereon and ensure that it had a certain roughness, and then the plate was ultrasonically cleaned with acetone and ethanol to remove the residual oil stains.

[0044] The tape was attached to the Ti-6Al-4V alloy plate with a certain gap and the coating thickness was 2 mm. Figure 1 (a); then apply the slurry to the gap and smooth it using a scraper, as shown in Figure 1 (b) As shown; the alloy plate was placed in a drying oven at 50°C for 4 hours, and then the tape was removed, as shown in FIG. Figure 1 (c) as shown.

[0045] 4) The dried powder and the substrate are laser clad to obtain a coating, wherein the laser cladding process parameters are: laser power of 3500 W, scanning speed of 600 mm / min, optical spot diameter of 3 mm, defocus of 25 mm, argon as protective gas, and gas flow rate of 5 L / min.

[0046] Example 2

[0047] This embodiment provides a refractory high entropy alloy coating by laser cladding on the surface of a titanium alloy, and the specific steps of preparation are:

[0048] 1) Weigh each metal powder according to mass percentage, specifically:

[0049] Mo: 15.0wt%, Ta: 29.0wt%, Nb: 14.0wt%, V: 7.0wt%, W: 31wt%;

[0050] Then the weighed metal powders were mixed and vacuum ball-milled for 2 h to obtain a mixed alloy powder of 50 μm.

[0051] 2) Add 5% by weight of anhydrous ethanol to the mixed alloy powder to obtain a slurry.

[0052] 3) The Ti-6Al-4V alloy plate was polished with 400-grit sandpaper to remove the oxide thereon and ensure that it had a certain roughness, and then the plate was ultrasonically cleaned with acetone and ethanol to remove the residual oil stains.

[0053] The tape was attached to the Ti-6Al-4V alloy plate with a certain gap and the coating thickness was 1 mm. Figure 1 (a); then apply the slurry to the gap and smooth it using a scraper, as shown in Figure 1 (b) As shown; the alloy plate was placed in a drying oven at 80°C for 2 hours, and then the tape was removed, as shown in FIG. Figure 1 (c) as shown.

[0054] 4) The dried powder and the substrate are laser clad to obtain a coating, wherein the laser cladding process parameters are: laser power of 3500 W, scanning speed of 600 mm / min, optical spot diameter of 3 mm, defocus of 25 mm, argon as protective gas, and gas flow rate of 5 L / min.

[0055] Example 3

[0056] This embodiment provides a refractory high entropy alloy coating by laser cladding on the surface of a titanium alloy, and the specific steps of preparation are:

[0057] 1) Weigh each metal powder according to mass percentage, specifically:

[0058] Mo: 17.0wt%, Ta: 31.0wt%, Nb: 16.0wt%, V: 9.0wt%, W: 33wt%;

[0059] Then the weighed metal powders were mixed and vacuum ball-milled for 5 h to obtain a mixed alloy powder of 20 μm.

[0060] 2) 10% by weight of anhydrous ethanol is added to the mixed alloy powder to obtain a slurry.

[0061] 3) The Ti-6Al-4V alloy plate was polished with 400-grit sandpaper to remove the oxide thereon and ensure that it had a certain roughness, and then the plate was ultrasonically cleaned with acetone and ethanol to remove the residual oil stains.

[0062] The tape was attached to the Ti-6Al-4V alloy plate with a certain gap and the coating thickness was 3 mm. Figure 1 (a); then apply the slurry to the gap and smooth it using a scraper, as shown in Figure 1 (b) As shown; the alloy plate was placed in a drying oven at 90°C for 1 hour, and then the tape was removed, as shown in FIG. Figure 1 (c) as shown.

[0063] 4) The dried powder and the substrate are laser clad to obtain a coating, wherein the laser cladding process parameters are: laser power of 3500 W, scanning speed of 600 mm / min, optical spot diameter of 3 mm, defocus of 25 mm, argon as protective gas, and gas flow rate of 5 L / min.

[0064] Experimental Example 1

[0065] The refractory high entropy alloy coating prepared in Example 1 was subjected to phase analysis to obtain an XRD diffraction pattern as shown below: Figure 2 It can be seen that the coating phases are mainly BCC solid solution, containing a small amount of intermetallic compounds, and the structure is relatively simple.

[0066] The sample prepared in Example 1 was cut into a cladding layer sample, which was ground and polished with 200-800 mesh metallographic sandpaper, and etched with an etching solution (HF:HNO3:H2O=1:2:7) for about 30 seconds. The cross-sectional morphology of the cladding layer was obtained under a scanning electron microscope. Figure 3 It was found that the coating structure was dense and uniform without obvious defects, the grains were mostly fine dendrites, and the coating was tightly bonded to the substrate.

[0067] The microhardness of the coating obtained in Example 1 was measured using a hVS-1000A microhardness tester, and the hardness curve was obtained as shown in FIG. Figure 4 The hardness value of the upper layer of the coating reaches up to 675.2hV 0.5 The average hardness of the coating can reach 636.31hV 0.5 ; Compared with the matrix, the hardness is increased by 77.2%.

[0068] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A laser cladding refractory high entropy alloy coating on the surface of titanium alloy. It is characterized in that Prepared from the following metal powders by mass percentage: Mo: 15.0-17.0wt%, Ta: 29.0-31.0wt%, Nb: 14.0-16.0wt%, V: 7.0-9.0wt%, W: 31-33wt%.

2. The titanium alloy surface laser cladding refractory high entropy alloy coating according to claim 1, It is characterized in that The mass percentages of the metal powder are Mo: 16.08wt%, Ta: 28.94wt%, Nb: 15.3wt%, V: 7.98wt%, and W: 31.7wt%.

3. The method for preparing a refractory high entropy alloy coating by laser cladding on the surface of a titanium alloy according to any one of claims 1 or 2, It is characterized in that The following steps are involved: 1) Weighing the metal powder raw materials according to the mass percentage, mixing them, and performing vacuum ball milling to obtain a mixed alloy powder; 2) mixing the mixed alloy powder with anhydrous ethanol to obtain a slurry; 3) The slurry is coated on the surface of the titanium alloy substrate and then dried and laser clad to obtain a high entropy alloy coating.

4. The preparation method according to claim 3, It is characterized in that The vacuum ball milling time in step 1) is 3-5 hours.

5. The preparation method according to claim 3, It is characterized in that The particle size of the mixed alloy powder in step 1) is 15-53 μm.

6. The preparation method according to claim 3, It is characterized in that In the step 2), the anhydrous ethanol is 5-10% of the mass of the mixed alloy powder.

7. The preparation method according to claim 3, It is characterized in that The coating thickness in step 3) is 1.0-3.0 mm.

8. The preparation method according to claim 3, It is characterized in that In the step 3), the drying temperature is 550-100° C. and the drying time is 2-5 hours.

9. The preparation method according to claim 3, It is characterized in that The process parameters of laser cladding in step 3) are: laser power of 3500 W, scanning speed of 600 mm / min, spot diameter of 3.0 mm, defocusing amount of 25 mm, argon as protective gas, and gas flow rate of 5 L / min.

10. The preparation method according to claim 3, It is characterized in that In the step 3), the titanium alloy substrate is pretreated before coating, and the pretreatment method is: the surface of the substrate is polished with 400-mesh sandpaper and then degreased.